2016
DOI: 10.1016/j.eurpsy.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Conversion to Bipolar Disorder in Unipolar Depressed Patients Participating in Trials on Antidepressants

Abstract: In a sample of middle-aged hospitalized unipolar depressed patients participating in trials on antidepressants, the risk of conversion was associated with the number of previous depressive episodes. Therefore, this study emphasizes that unipolar depressed patients experiencing a relatively high number of recurrences should be followed more closely, or at least be informed about the possible increased risk of conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 51 publications
0
12
0
1
Order By: Relevance
“…However, when Prisciandaro and Tolliver [73] recently evaluated the psychometric properties of the MADRS in bipolar depression, significant measurement problems were identified. In contrast, by means of DIF analysis, we have shown that HAM-D 6 has the same good psychometric properties in bipolar depression as in unipolar depression [24,26]. HAM-D 6 can, therefore, be considered as a suitable alternative to MADRS in the measurement of bipolar depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when Prisciandaro and Tolliver [73] recently evaluated the psychometric properties of the MADRS in bipolar depression, significant measurement problems were identified. In contrast, by means of DIF analysis, we have shown that HAM-D 6 has the same good psychometric properties in bipolar depression as in unipolar depression [24,26]. HAM-D 6 can, therefore, be considered as a suitable alternative to MADRS in the measurement of bipolar depression.…”
Section: Discussionmentioning
confidence: 99%
“…However, the studies by Kyle et al [21], Licht et al [18], and Bobes et al [23] only considered patients with unipolar depression. To assess whether the unipolar/bipolar “mixing” of these populations introduced a bias, we performed a differential item functioning (DIF) analysis of the Holmskov et al [24] study in which 35 of the 102 patients (34%) in the original Danish University Antidepressant Group (DUAG) [25] study had converted to bipolar disorder. This DIF analysis showed that there was no bias in this respect.…”
Section: Resultsmentioning
confidence: 99%
“…Conflicting results were obtained for the scalability of the unstructured version of the HAM-D 17 . Mokken coefficients ranging from 0.24 [172] to 0.35 [169] were found, indicating that the HAM-D 17 is a multidimensional rating scale. Similarly, Bobes et al [98] and Kyle et al [100] questioned the scalability of the unstructured version of the HAM-D 21 .…”
Section: Scalability Of the Different Versions Of The Ham-dmentioning
confidence: 99%
“…Bech and his research group conducted a number of studies in which they analyzed the scalability of the various versions of the HAM-D [14,20,96,98,100,[165][166][167][168][169][170][171][172]. In these studies, including a recent paper by da Silva et al [173], the HAM-D 6 was found to have an excellent level of scalability with Mokken coefficients ranging from 0.42 [172] to 0.65 [169]. Studies using the Rasch analysis further confirmed the scalability of the unstructured version of the HAM-D 6 [96,165,170].…”
Section: Scalability Of the Different Versions Of The Ham-dmentioning
confidence: 99%
“…While major depressive disorder is more common and bipolar disorder more rare, distinguishing the two is clinically difficult as they share many common features, especially during depressive episodes (Phillips and Kupfer, 2013). Indeed, a recent study by Holmskov et al (2016) found that 1 in 5 participants in clinical trials for antidepressants underwent a diagnostic conversion from unipolar depression to bipolar depression over time. This means that a substantial number of people with bipolar disorder were actually misdiagnosed, sometimes for years.…”
mentioning
confidence: 99%